Studies in the Basidiodendron caesiocinereum complex (Auriculariales, Basidiomycota) - Spirin, Viacheslav; Malysheva, Vera; Schoutteten, Nathan; Viner, Ilya; Miettinen, Otto; Nordén, Jenni; Ryvarden, Leif; Kotiranta, Heikki; Verbeken, Annemieke; Weiß, Michael; Larsson, Karl-Henrik (Mycological progress, 2021)
Taxonomy of Basidiodendron caesiocinereum complex is revised based on morphological and molecular methods (with the use of nc LSU rDNA, ITS and TEF1 regions). The basidiospore ornamentation is justified as a key morphological character for the species recognition in the group. As redefined here, B. caesiocinereum is an angiosperm-dwelling species with smooth basidiospores. Bourdotia cinerella and B. cinerella var. trachyspora are proved to represent separate species with warted basidiospores; they are reintroduced as Basidiodendron cinerellum and B. trachysporum . Additionally, eight new species related to B. caesiocinereum are described based on material from Eurasia, North America and Africa, and identity of B. spinosum from Oceania is discussed.